A Discrete Element Framework for the modelling of rock-filled gabions. Issue 1 (August 2021) - Marigo, Nicola; Gabrieli, Fabio; Pol, Antonio; Bisson, Alberto; Brezzi, Lorenzo
Abstract: Gabions are steel mesh cages filled with stones. Recently, they have had a great diffusion for numerous applications such as erosion control and soil retention along cuts and natural slopes. The study of their mechanical behaviour under different loading conditions is a fundamental prerequisite for an improved understanding of their overall performance and in a design perspective. In this respect, the Discrete Element Method (DEM) appears a robust and effective technique. The DEM is particularly suited for modelling granular materials, and recently it has efficiently been applied for modelling deformable structures such as welded meshes. This work presents a discrete framework for the modelling of rock-filled gabions. The gabion module is modelled as an assembly of deformable cylindrical elements, while the filling material is represented using rigid aggregates of spherical particles. The tensile behaviour of the gabion elements is set in order to fit the mechanical response of the steel bars adopted in practice. The model is applied to analyse a uniaxial compression test on a single gabion.